MENINGKATKAN MOTIVASI BELAJAR DENGAN MENERAPKAN GROUP INVESTIGATION DI SMPN 3 BUKITTINGGI - Reza Olivia; Jagar Lumban Toruan; Ardipal Ardipal (SENDRATASIK UNP, 2012)
The purpose of this research is to describe the processes of student motivation improvement in learning local folk music of the 7th grader in SMP Negeri 3 junior high school Bukittinggi by applying “cooperative learning, the group investigation type.” This kind of research is class action research. The datum to be observed in this research are from practical examination by playing local folk music using instrument, observing student motivation, assessing student motivation and doing field note. The research is done in two cycles, cycle I and cycle II. Each of them has two meetings. Every cycle consists of four events which are planning, action, observation, and reflection.